2003
DOI: 10.1021/ma035551z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valence and Chemical Species of Added Electrolyte on Polyelectrolyte Conformations and Interactions

Abstract: The effect of added electrolyte (AE) valence and species on polyelectrolytes was studied using automatic, continuous mixing (ACM), allowing measurements over composition gradients. The second virial coefficient A 2 was decomposed into contributions from an electrostatically sensitive meansquare gyration radius 〈S 2 〉 and an external electrostatic field. 〈S 2 〉 matched predictions of combined electrostatic persistence length and excluded-volume theories, without adjustable parameters. A2 was modeled via an equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…At higher molecular weights this model may be in principle biased by the neglect of the interactions of the distant monosaccharide units and allowed intersection of the polymer chain, which might cause smaller Rg values of the simulated molecules. However, the experimentally determined radius of gyration of a 1.8MDa molecule in 0.1M NaCl (Sorci & Reed, 2004) is about 1760 Å while the simulated values are 1530 Å for 0.2M NaCl and 1720 Å for just neutralized system. Considering the effect of electrolyte concentration on Rg (see also section 3.3.…”
Section: 2the Shape and Dimensions Of The Macromoleculesmentioning
confidence: 81%
See 1 more Smart Citation
“…At higher molecular weights this model may be in principle biased by the neglect of the interactions of the distant monosaccharide units and allowed intersection of the polymer chain, which might cause smaller Rg values of the simulated molecules. However, the experimentally determined radius of gyration of a 1.8MDa molecule in 0.1M NaCl (Sorci & Reed, 2004) is about 1760 Å while the simulated values are 1530 Å for 0.2M NaCl and 1720 Å for just neutralized system. Considering the effect of electrolyte concentration on Rg (see also section 3.3.…”
Section: 2the Shape and Dimensions Of The Macromoleculesmentioning
confidence: 81%
“…In both these studies the dependences of Rg and intrinsic viscosity on molecular weight as well as the scaling factors of both the quantities were determined. Sorci & Reed (2004) studied hyaluronan solutions at varying concentrations of NaCl and CaCl2 up to the ionic strength of 0.1 M. They showed a continuous decrease of the radius of gyration with growing ionic strength as well as the formation of smaller coils in CaCl2 with respect to NaCl. Buhler & Boué (2004) showed that the persistence length of a hyaluronan molecule decreases with growing ionic strength of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…The polyelectrolyte characteristics that affect the polyelectrolyte solution properties are the chemical structure of the monomer units, the chain length, the charge density, the type of the ionic groups, polyelectrolyte concentration, and so forth 5–11. The counterions influence the polyelectrolyte solution properties by their size, valency and polarizability, and the water structure around the counterion 12–16. With respect to the medium properties, the ionic strength and solvent polarity may exert a significant effect on the polyelectrolyte solution 17–25.…”
Section: Introductionmentioning
confidence: 99%
“…Strong differences in the solution to V for symmetric versus asymmetric salts and for monovalent versus higher valence salts begin to grow as zeV/k B T grows greater than its linearization constraint [37].…”
Section: Poisson-boltzmann Equation and The Debye Screening Lengthmentioning
confidence: 99%